2008
DOI: 10.1111/j.1365-3083.2008.02142.x
|View full text |Cite
|
Sign up to set email alerts
|

The Long‐term Impaired Macrophages Functions are Already Observed Early after High‐dose Ethanol Administration

Abstract: Herein, we described an experimental model of high‐dose ethanol (EtOH) administration, able to induce in vitro impairment in macrophage phagocytic capacity, already observed at 24 h after the last EtOH administration. This phenomenon was characterized by enlarged time required for adhesion and internalization events. Parallel studies documented an overall impaired production of interleukin (IL)‐6 and nitric oxide (NO) production by peritoneal macrophages in EtOH‐treated mice following interferon (IFN)‐γ and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…A significant reduction in superoxide ion and nitrite ion release was observed when RAW 264.7 macrophages were exposed to SPD‐MAA. Alcohol has been previously reported to reduce phagocytic function, antimicrobial activity, superoxide ion, and nitric oxide release from macrophages (Andrade et al., ; Castro et al., ; D'Souza et al., ; Libon et al., ; Satapathy and Shrivastava, ; Szabo, ). Our findings may suggest MAA adduct formation could be one of the mechanisms through which alcohol may exert such actions.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction in superoxide ion and nitrite ion release was observed when RAW 264.7 macrophages were exposed to SPD‐MAA. Alcohol has been previously reported to reduce phagocytic function, antimicrobial activity, superoxide ion, and nitric oxide release from macrophages (Andrade et al., ; Castro et al., ; D'Souza et al., ; Libon et al., ; Satapathy and Shrivastava, ; Szabo, ). Our findings may suggest MAA adduct formation could be one of the mechanisms through which alcohol may exert such actions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports from our group demonstrated that high-dose ethanol (EtOH) administration is able to induce an allergic-type inflammatory response in function of enhanced levels of seric IgE, high levels of gastric interleukin (IL)-4 and increased IL-4 synthesis by splenic T cells after in vitro unspecific stimulus (concanavalin A) (Andrade et al, 2006(Andrade et al, , 2008(Andrade et al, , 2009). This allergic-type reaction in the GALT can disturb pathways involved in the establishment of regulatory mechanisms, hindering oral tolerance.…”
mentioning
confidence: 98%
“…Previous reports from our group described a reliable model of acute high‐dose alcohol consumption (4.5 mg/kg during 4 consecutive days) and showed that ethanol affects several immunological functions [14, 15]. Our data demonstrated that changes on macrophage functions, including phagocytic capacity, inflammatory cytokine synthesis and NO production, can be observed as early as 24 h after high‐dose short‐term ethanol administration and that they are maintained for up to 30 days thereafter [15].…”
Section: Introductionmentioning
confidence: 57%
“…We have reported that short‐term administration of high doses of ethanol induce an allergy‐like immune profile in C57BL/6 mice [14] and had a negative impact in the phagocytic capacity of peritoneal macrophages [15]. Herein, using the same model, we focused our investigation on the effects of alcohol in the antigen‐presenting ability of ‘classical’ APC such as macrophages, DC and B cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation